A novel raw material for geopolymers: Coal-based synthetic natural gas slag. (20th July 2020) - Sha, Dong; Pan, Baofeng; Sun, Yiren
Abstract: Coal-based synthetic natural gas slag (CSNGS) is a by-product obtained from coal-based synthetic natural gas technology, and its output is increasing year by year. To divert CSNGS from hazardous waste stream to beneficial uses, the present study aims to propose a novel method by using the CSNGS as a raw material to fabricate the geoploymer under the alkali activation of sodium hydroxide solution. The effects of different factors such as water-solid ratio, activator concentration, raw material particle size, thermal curing temperature and duration on the strength of the CSNGS geopolymer were investigated by an orthogonal test. Microstructural features of the optimized CSNGS geopolymer were also evaluated via X-ray diffraction (XRD), field emission scanning electron microscope-energy dispersive spectrometer (FESEM/EDS), Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analyzer (TG), mercury intrusion porosimetry (MIP) tests. The obtained results showed that the mechanical properties of geopolymers were mainly affected by the thermal curing temperature. When raising the curing temperature from 65 °C to 95 °C, more active components facilitated more reaction products (N-A-S-H), which led to a denser microstructure and changes in Si–O-T bonds, an increasing Si/Al ratio from 2.06 to 2.87, and a decreasing porosity with 29.2%. It was also found that the suitable range of the activator concentrations for CSNGS geopolymers were 6–9 mol/L. Also, the results of FT-IR and TG showed that significant carbonation could be produced when the activator concentration exceeded this range. For the CSNGS geopolymer, the 28 days compressive strength was 36.1 MPa at the optimal synthesis conditions. The findings of the study suggested that CSNGS can be used as a raw material for geopolymer cement manufacturing, which is beneficial for resource conservation, environmental protection, and cleaner production. Highlights: Coal-based synthetic natural gas slag (CSNGS) was proposed to fabricate geopolymers. The curing temperature had the greatest effect on the strength of CSNGS geopolymers. The high concentration of activator tends to cause carbonization of the geopolymers. The strength of geopolymers was increased by the increase of the Si/Al. SEM and MIP results showed a denser structure with an increase of curing temperature.